Web 2.0 the global SOA. - Hinchcliffe, Dion (SOA webservices journal.)
The subject of Web 2.0 has become profoundly important over the last year. Web 2.0 describes the next generation of the Web as an application platform where most of a user's software experience resides. The subject is somewhat controversial, but it's becoming ever more apparent as the successor to monolithic system architecture, prepackaged software and traditional Web applications.